The patriarch : the remarkable life and turbulent times of Joseph P. Kennedy - Nasaw, David (2012)
Historian David Nasaw brings to life the story of Joseph Patrick Kennedy, in this, the first and only biography based on unrestricted and exclusive access to the Joseph P. Kennedy papers
East Boston to Cambridge to Brookline -- Hollywood -- Washington -- London -- Washington, but briefly -- Palm Beach and Hyannis Port
Includes bibliographical references (pages [829]-834) and index
Keywords: Kennedy, Joseph P. -- 1888-1969; Kennedy family; Ambassadors -- United States -- Biography; Politicians -- United States -- Biography; Businesspeople -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Biography